America's private forests : - Best, Constance (Island Press, 2001)
The book identifies the major threats to private forests in the United State, considers barriers to conservation, outlines the available tools and programs for promoting conservation, presents a "road map" to guide collective efforts for the conservation of private forests and their native biodiversity